Comparing spiking and slow wave activity from invasive electroencephalography in patients with and without seizures. Issue 5 (May 2018) - Lundstrom, Brian Nils; Meisel, Christian; Van Gompel, Jamie; Stead, Matt; Worrell, Greg
Highlights: Intracranial EEG is systematically compared between patient groups with and without seizures. Sharply contoured EEG activity may be more prevalent than expected in patients without seizures. EEG spiking and slow waves differ between patient groups with differing seizure probabilities. Abstract: Objectives: To develop quantitative measures for estimating seizure probability, we examine intracranial EEG data from patient groups with three qualitative seizure probabilities: patients with drug resistant focal epilepsy (high), these patients during cortical stimulation (intermediate), and patients who have no history of seizures (low). Methods: Patients with focal epilepsy were implanted with subdural electrodes during presurgical evaluation. Patients without seizures were implanted during treatment with motor cortex stimulation for atypical facial pain. Results: The rate and amplitude of spikes correlate with qualitative seizure probability across patient groups and with proximity to the seizure onset zone in focal epilepsy patients. Spikes occur earlier during the negative oscillation of underlying slow activity (0.5–2 Hz) when seizure probability is increased. Similarly, coupling between slow and fast activity is increased. Conclusions: There is likely a continuum of sharply contoured activity between non-epileptiform and epileptiform. Characteristics of spiking and how spikes relate to slow activity can be combined to predict seizure onset zones. Significance: Intracranial EEG data from patients without seizures represent a unique comparison group and highlight changes seen in spiking and slow wave activity with increased seizure probability. Slow wave activity and related physiology are an important potential biomarker for estimating seizure probability.